Seismic Performance Analysis on Different Plan Configuration of Multi-Storeyed Building Using Rocking Shear Wall - Devyani Mali, Jagruti Patil, Ankita Thorat, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Over the last few years, Studies have noted damaging avoidance design ideology as an alternative to conventional design ideas, as these are an intrinsically significant detriment. In order to achieve this, the self-centering damage avoidance rocking system, an approach for restricting seismic forces to structures coupled with energy dissipating technology and restoring force systems has been developed. The seismic behavior of rocking mechanisms on precast segmental bridge abutments, shear walls, and steel braced frames have been the subject of several research. A few works have recently explored the behavior of the rocking systems, although there are still questions regarding the specifics and responsiveness of this system. Thus, the purpose of this paper is to examine the application of rocking shear walls in G+14 multi-storeyed residential buildings with a variety of plan configurations, such as rectangular, C-shape, and T-shape, all of which have the same floor area, as well as to investigate the nature of the earthquake-exposed structure by using non-linear time history analysis. Using well-known FEM integrated software called ETABs 2018, the analysis and modelling for SMRF building (three cases of rocking structures, three cases of conventional shear walls, and three reinforced concrete bare frames) is carried out in seismic zone III of India as mandated by IS 1893 (Part-1)-2016. It is concluded that structures with rocking shear walls will perform better in terms of all seismic characteristics like storey drift, storey displacements and base shears than structures with traditional shear walls.